Model and field tests of drilled displacement system piles - Zhussupbekov A.; Dhanya J.S.; Issakulov A.; Omarov A.; Iskakov S.; Mukhanov D. (E3S Web of Conferences, 2023)
Drilled Displacement System (DDS) and Continuous Flight Auger (CFA) piles are two popular techniques used for building pile foundations that offer advantages over traditional pile systems, including improved load-carrying capacity, reduced installation time, and less spoil generation. This article presents laboratory-scaled model tests conducted on model piles installed using the Drilled Displacement System (DDS) and Continuous Flight Auger (CFA) technologies on a test tank setup filled with soil. Model piles considering a scaling factor of 1/20 with a diameter of 20 mm and a length of 300 mm were adopted for the study. Static loading is applied to the model piles and the corresponding displacements are measured during each loading phase. The results of the analysis were compared for load-settlement curves and ultimate bearing capacity estimates for both DDS and CFA piles. Based on the study, the DDS piles were observed to perform well in terms of load-carrying capacity compared to the CFA piles. Further, full-scale field tests under static load conditions were carried out on DDS-drilled piles of diameter 400 mm and length 6 m. The load-settlement response from the field test shows good agreement with the model tests. Overall, the results of the study provide valuable insights into the behavior and performance of DDS piles that can be used to optimize their design and installation in different soil types.